The effect of guanfacine treatment on ocular parameters in pediatric and adolescents patients with attention-deficit/hyperactivity disorder - Işıl Merve Torun; Zeynep Vatansever Pinar; Şeyma İlhan (BMC Ophthalmology)
Abstract Background This study aimed to evaluate the effects of guanfacine on the anterior and posterior segments of the eye. Methods This prospective study included 32 children and adolescents with Attention-deficit/hyperactivity disorder (ADHD). The participants underwent a detailed ophthalmologic evaluation before and 6 months after the beginning of guanfacine treatment. The following data were recorded for each participant: refraction error, intraocular pressure (IOP), anterior chamber depth (ACD), central corneal thickness (CCT), corneal aberrations using corneal topography, retinal nerve fiber layer (RNFL) analysis of seven quadrants (central, nasal, naso-superior, naso-inferior, temporal, temporo-superior, temporo-inferior), central macular thickness (CMT), and choroidal thickness (CT). Assessments were made of these parameters obtained from images using an optical coherence tomography (OCT) instrument. Results A significant increase in total root mean square (RMS) (p = 0.029*), RMS low-order aberration (LOA) (p = 0.014*), Coma 0° (p < 0.001*), and Coma 90° (p = 0.037*) corneal aberrations was observed at the sixth month of guanfacine treatment in comparison with the baseline examination. Other ocular parameters demonstrated no significant change from the baseline examination findings at the sixth month of guanfacine treatment. (p > 0.05, for each). Conclusion Oral guanfacine in the treatment of ADHD had no effect on ocular structures such as the retina, choroid, optic nerve, refraction, or corneal thickness, although it increased corneal aberrations. The results require support through further studies with extended follow-up and a larger patient group.